Implementasi dan Analisis Keamanan Jaringan Pada STIA Lancang Kuning Dumai Menggunakan Port Scanning dan Firewall Tarpit - Suhaidi, Mustazzihim; Nurhadi, Nurhadi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to implement and analyze network security at STIA Lancang Kuning Dumai in Dumai City using the port scanning method and tarpit firewall. The main purpose of this research is to identify security holes in the network and protect the system from threats that may arise. The method used in this research is the SDLC method. The results of the analysis show that the implementation of port scanning and firewall tarpit at STIA Lancang Kuning Dumai has succeeded in significantly increasing network security. The port scan was able to identify several security holes which were then able to be fixed and strengthened. Tarpit firewalls are also effective in inhibiting attacks by slowing down and limiting attacker access. This research makes an important contribution to securing the network at STIA Lancang Kuning Dumai and provides valuable guidance for similar institutions in strengthening their security systems. However, it is important to continuously monitor new technology developments and security threats to keep systems well-protected and ready for more sophisticated attacks in the future.